Functional Consequences of the Postnatal Switch From Neonatal to Mutant Adult Glycine Receptor α1 Subunits in the Shaky Mouse Model of Startle Disease - Schaefer, Natascha; Zheng, Fang; van Brederode, Johannes; Berger, Alexandra; Leacock, Sophie; Hirata, Hiromi; Paige, Christopher J.; Harvey, Robert J.; Alzheimer, Christian; Villmann, Carmen (Frontiers in Molecular Neuroscience, 2018)
Mutations in GlyR α1 or β subunit genes in humans and rodents lead to severe startle disease characterized by rigidity, massive stiffness and excessive startle responses upon unexpected tactile or acoustic stimuli. The recently characterized mouse startle disease mutant shaky carries a missense mutation (Q177K) in the β8-β9 loop within the large extracellular N terminal domain of the GlyR α1 subunit. This results in a disrupted hydrogen bond network around K177 and faster GlyR decay times. Symptoms in mice start at postnatal day 14 and increase until premature death of homozygous shaky mice around 4-6 weeks after birth. Here we investigate the in vivo functional effects of the Q177K mutation using behavioral analysis coupled to protein biochemistry and functional assays. Western blot analysis revealed GlyR α1 subunit expression in wildtype and shaky animals around postnatal day 7, a week before symptoms in mutated mice become obvious. Before two weeks of age, homozygous shaky mice appeared healthy and showed no changes in body weight. However, analysis of gait and hind-limb clasping revealed that motor coordination was already impaired. Motor coordination and the activity pattern at P28 improved significantly upon diazepam treatment, a pharmacotherapy used in human startle disease. To investigate whether functional deficits in glycinergic neurotransmission are present prior to phenotypic onset, we performed whole-cell recordings from hypoglossal motoneurons (HMs) in brain stem slices of wildtype and mutant mice at different postnatal stages. Shaky homozygotes showed a decline in mIPSC amplitude and frequency at P9-P13, progressing to significant reductions in mIPSC amplitude and decay time at P18-24 compared to wildtype littermates. Extrasynaptic GlyRs recorded by bath-application of glycine also revealed reduced current amplitudes for shaky compared to wildtype neurons, suggesting that presynaptic GlyR function is also impaired. Thus, a distinct, but behaviorally not yet effective impairment of glycinergic synapses precedes the symptoms onset in shaky mice. These findings extend our current knowledge on startle disease in the shaky mouse model in that they demonstrate how the progression of GlyR dysfunction entails, with a delay of about one week, the appearance of disease symptoms.